3x-2+x=10-2x

Simple and best practice solution for 3x-2+x=10-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2+x=10-2x equation:


Simplifying
3x + -2 + x = 10 + -2x

Reorder the terms:
-2 + 3x + x = 10 + -2x

Combine like terms: 3x + x = 4x
-2 + 4x = 10 + -2x

Solving
-2 + 4x = 10 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-2 + 4x + 2x = 10 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-2 + 6x = 10 + -2x + 2x

Combine like terms: -2x + 2x = 0
-2 + 6x = 10 + 0
-2 + 6x = 10

Add '2' to each side of the equation.
-2 + 2 + 6x = 10 + 2

Combine like terms: -2 + 2 = 0
0 + 6x = 10 + 2
6x = 10 + 2

Combine like terms: 10 + 2 = 12
6x = 12

Divide each side by '6'.
x = 2

Simplifying
x = 2

See similar equations:

| 5(x+2)=4(9-2x) | | 3+5(5t+1)+8t= | | 4*a-2*1+11=6*a-13 | | 2(x+4)=3(6-x) | | 9*w-2*w+8=4*w+38 | | 3-6x=7-7x | | 7(x+4)=5(x-3) | | 2*m+6=2*m-1 | | (4m+3)9+6m= | | 6*n+21=4*n+57 | | 2+(6m+3)7= | | 6(x+1)=4(x-2) | | 9+9(5+4m)= | | 7(3x+3)=4(4x-1) | | 4+6(3m+2)= | | q+5=2*q+7 | | 3(4x+2)=2(5x-2) | | 4*x+11=x+2 | | 2(2x+3)=3(x+1) | | 6m+7(7m+9)= | | 3x-3=9-x | | 14*k+16*k+88=163 | | 2r-8+4=5(r+1) | | 23+x=2-2x | | 3(2x-4)=2(x-2) | | 3(1+4m)+5m= | | 5(x-2)=4(x-3) | | 1-x=x-1 | | 5-x=x-4 | | 3-5x=4x-6 | | 2*c+6*c+8=32 | | 2x-4=11-x |

Equations solver categories